The Effectiveness Of Leadership In Change Management To Improve The Quality Of Education At MI Darul Jihad Mataba Sana-Laok Waru Pamekasan - Abd Halim (Penerbit Presisi Pustaka, 2026)
Leadership is a key factor in determining the success of change management in Islamic educational institutions. This article aims to analyze the effectiveness of leadership in managing change to improve the quality of education at MI Darul Jihad Mataba Sana-Laok Waru Pamekasan. This research uses a qualitative approach with a field research method through observation, in-depth interviews, and documentation. The results show that leadership effectiveness is determined by the leader's ability to formulate a vision for change, build effective communication, and involve all institutional elements in the transformation process. Furthermore, adaptive and participatory leadership can create an innovative organizational culture that is responsive to change. This article emphasizes that the success of change management in improving educational quality largely depends on visionary and contextual leadership. Theoretically, this study contributes to enriching the discourse on transformational leadership within the context of Islamic education. Practically, it offers a replicable leadership model for principals and school leaders seeking to drive quality improvement through structured change management in Islamic educational institutions.